Acute inhibition of a cortical motor area impairs vocal control in singing zebra finches. (29th October 2014) - Yazaki‐Sugiyama, Yoko; Yanagihara, Shin; Fuller, Patrick M.; Lazarus, Michael
Abstract Genetically targeted approaches that permit acute and reversible manipulation of neuronal circuit activity have enabled an unprecedented understanding of how discrete neuronal circuits control animal behavior. Zebra finch singing behavior has emerged as an excellent model for studying neuronal circuit mechanisms underlying the generation and learning of behavioral motor sequences. We employed a newly developed, reversible, neuronal silencing system in zebra finches to test the hypothesis that ensembles of neurons in the robust nucleus of the arcopallium (RA) control the acoustic structure of specific song parts, but not the timing nor the order of song elements. Subunits of an ivermectin‐gated chloride channel were expressed in a subset of RA neurons, and ligand administration consistently suppressed neuronal excitability. Suppression of activity in a group of RA neurons caused the birds to sing songs with degraded elements, although the order of song elements was unaffected. Furthermore some syllables disappeared in the middle or at the end of song motifs. Thus, our data suggest that generation of specific song parts is controlled by a subset of RA neurons, whereas elements order coordination and timing of whole songs are controlled by a higher premotor area.